2022
DOI: 10.1099/mgen.0.000817
|View full text |Cite
|
Sign up to set email alerts
|

Prophage-mediated genome differentiation of the Salmonella Derby ST71 population

Abstract: Although Salmonella Derby ST71 strains have been recognized as poultry-specific by previous studies, multiple swine-associated S. Derby ST71 strains were identified in this long-term, multi-site epidemic study. Here, 15 representative swine-associated S. Derby ST71 strains were sequenced and compared with 65 (one swine-associated and 64 poultry-associated) S. Derby ST71 strains available in the NCBI database at a pangenomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Certain bacterial species that are widely distributed in various environments usually have an open pan-genome, in which new genes can confer beneficial effects for environmental adaptation [ 47 ]. On the other hand, species that tend to occupy limited habitats frequently have a closed pan-genome because they do not need to respond to many environmental changes [ 48 , 49 ]. Our results demonstrated that L. salivarius species harbor a closed pan-genome, similar to that in L. ruminis [ 50 ].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Certain bacterial species that are widely distributed in various environments usually have an open pan-genome, in which new genes can confer beneficial effects for environmental adaptation [ 47 ]. On the other hand, species that tend to occupy limited habitats frequently have a closed pan-genome because they do not need to respond to many environmental changes [ 48 , 49 ]. Our results demonstrated that L. salivarius species harbor a closed pan-genome, similar to that in L. ruminis [ 50 ].…”
Section: Discussionmentioning
confidence: 62%
“…The higher abundance of GT2 and GT8 families in the strains from badgers may benefit the host by regulating gut microbiota homeostasis through the production of polysaccharides [ 59 ]. Besides plasmids, prophages are an important source of the gene gain events which play a critical role in bacterial population evolution [ 49 ]. Most of the prophage sequences identified in these badger-originated strains did not show high similarity to other analyzed L. salivarius genomes (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to be highly variable and differentially conserved among strains, making them key drivers of genome diversification and useful markers for serovar typing [126,127], Similarly, we conclude that in X. griffiniae prophages are major drivers of subspeciation and strain differentiation.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, X. griffiniae prophage regions reduced pairwise dDDH values among them by three percentage points. In Salmonella enterica prophage sequences have been shown to be highly variable and differentially conserved among strains, making them key drivers of genome diversification and useful markers for serovar typing [126, 127], Similarly, we conclude that in X. griffiniae prophages are major drivers of subspeciation and strain differentiation.…”
Section: Discussionmentioning
confidence: 81%